Flexural Behavior and Design Calculation Method of Joints With Bar Details Connecting T-Shaped Beam - Zhengxing Chen; Jianbo Mao; Linhai Zhang (Advances in Civil Engineering)
To design the bar connection details of joints more scientifically and address the variability of joint sizes in actual construction, this paper examined the force transmission mechanisms of linear bar, hooped-bar, and headed-bar joints. In doing so, it aimed to ensure the efficient completion of the project, while enhancing the bearing capacity and ductility of T-shaped beams. Bending tests were carried on 10 specimens and finite element analysis (FEA) was carried out on 17 specimens to investigate the effects of steel bar connection form, lap length, arrangement method, and joint shape on capacity and ductility. Based on the test and analysis results, it has been found that the joint performance of hooped-bar joints is optimal. When the single-side lap length was reduced to 120 mm (10 d), both bearing capacity and ductility improved. Furthermore, when hooped-bar was arranged in staggered manner, the bearing capacity and ductility outperformed those of an overlapping arrangement. The lap length for headed-bar joints should not be less than 120 mm and lap length below 150 mm are not recommended. Additionally, whether the joint shape was designed to be T-shaped or rectangular had only a slight effect on the mechanical properties of the joints. On this basis, this paper further combined the equations from the Chinese standard JTG/T 3365-05-2022 to propose design recommendations for the lap length and spacing of hooped-bar joints in staggered arrangements. Considering the test results alongside the specifications in ACI 318-11 and AIJ 2010, it was suggested that the lap length for headed-bar joints in the practical engineering mentioned in this paper should not be less than 150 mm. To ensure that the material was fully utilized and that the headed-bar joints had good resistance, a lap length within the range of 183–240 mm was recommended.